2021
DOI: 10.3390/molecules26133789
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Method for Quantification of Favipiravir as COVID-19 Management in Spiked Human Plasma

Abstract: In the current work, a simple, economical, accurate, and precise HPLC method with UV detection was developed to quantify Favipiravir (FVIR) in spiked human plasma using acyclovir (ACVR) as an internal standard in the COVID-19 pandemic time. Both FVIR and ACVR were well separated and resolved on the C18 column using the mobile phase blend of methanol:acetonitrile:20 mM phosphate buffer (pH 3.1) in an isocratic mode flow rate of 1 mL/min with a proportion of 30:10:60 %, v/v/v. The detector wavelength was set at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…[ 2 , 8 ] FPV was lately indicated for the treatment of COVID‐19 infections in various countries, including Russia, Egypt, KSA, UAE, Italy, India, Japan, and Turkey. [ 9 , 10 ] Literature review reveals few reported methods for analysis of FPV such as spectrophotometry, [ 11 ] spectrofluorimetry, [ 3 , 12 ] liquid chromatography, [ 3 , 13 , 14 , 15 , 16 ] and electrochemical methods. [ 17 , 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 8 ] FPV was lately indicated for the treatment of COVID‐19 infections in various countries, including Russia, Egypt, KSA, UAE, Italy, India, Japan, and Turkey. [ 9 , 10 ] Literature review reveals few reported methods for analysis of FPV such as spectrophotometry, [ 11 ] spectrofluorimetry, [ 3 , 12 ] liquid chromatography, [ 3 , 13 , 14 , 15 , 16 ] and electrochemical methods. [ 17 , 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazine carboxamide is a derivative that exhibits antiviral activity against RNA A literature survey revealed that no stability-indicating method has been reported yet for the quantitative determination of favipiravir impurities. A few analytical methods were found; those various experiments were performed in human plasma using LC-MS/MS and HPLC techniques (Balu & Paresh, 2021;Eryavuz et al, 2021;Hailat et al, 2021;Ibrahim et al, 2021;Katharina et al, 2021;Marzouk et al, 2022;Mikhail et al, 2021;Mohamed et al, 2021;Nakayama & Ryo, 2021;Nazifa Sabir Ali et al, 2021;Nippes et al, 2021;Pallavi & Kamalkishor, 2021;Ramarao & Abhinandana, 2021;Rezk et al, 2021;Srinivas, et al, 2021) (Table 1). The literature does not report any HPLC method that accurately and quantitatively assesses the relative and degradation impurities of favipiravir.…”
mentioning
confidence: 99%
“…A few reported methods were developed for determination of favipiravir in biological matrices. To the best of our knowledge, there is only one reported HPLC/UV method for favipiravir determination in biological samples, but it is not sufficiently sensitive for determining therapeutic levels of favipiravir in plasma due to the limited sensitivity and the high LOQ [35] . The other published methods adopted for favipiravir determination in biological matrices were LC-MS/MS, voltammetry and spectrofluorimetry as indicated in Table 4 .…”
Section: Comparison Between the Developed Methods And Reported Methods For Favipiravir Determination In Biological Matricesmentioning
confidence: 99%
“… LC-MS/MS 100–20000 7.11 100 [13] Human serum Protein precipitation by acetonitrile using 900 µL of serum. LC-MS / MS 48–50000 8.00 48 [35] Human urine None using 500 µL of urine. SW-AdSV 10–100 100–20000 ≤8.80 9.30 76 [36] Human plasma None using 20 µL of plasma.…”
Section: Comparison Between the Developed Methods And Reported Methods For Favipiravir Determination In Biological Matricesmentioning
confidence: 99%